2018
DOI: 10.1007/s00213-018-5063-9
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine, serotonin and norepinephrine releasing activities of a series of methcathinone analogs in male rat brain synaptosomes

Abstract: Rationale.-Novel synthetic 'bath salt' cathinones continue to appear on the street as abused and addictive drugs. The range of subjective experiences produced by different cathinones suggests that some compounds have primarily dopaminergic activity (possible stimulants) while others have primarily serotonergic activity (possible empathogenics). An understanding of the structure activity relationships (SARs) of these compounds will help in assessing the likely behavioral effects of future novel structures, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Therefore, although it is widely accepted that in rats compounds with high DAT selectivity are potent forward locomotor stimulators (Baumann et al 2011;Blough et al 2019), our data suggest that vertical locomotor activity in mice could be Effects of c 3-CMC (100-300 μM) and f 4-CMC (100-300 μM) on the integrity of cell membranes after 48-h incubation measured with LDH test. Data presented as mean ± standard error of the mean (SEM) from at least 3 independent experiments and expressed as a percentage of positive control group considered 100% cytotoxicity.…”
Section: -Meo-pvpmentioning
confidence: 61%
See 2 more Smart Citations
“…Therefore, although it is widely accepted that in rats compounds with high DAT selectivity are potent forward locomotor stimulators (Baumann et al 2011;Blough et al 2019), our data suggest that vertical locomotor activity in mice could be Effects of c 3-CMC (100-300 μM) and f 4-CMC (100-300 μM) on the integrity of cell membranes after 48-h incubation measured with LDH test. Data presented as mean ± standard error of the mean (SEM) from at least 3 independent experiments and expressed as a percentage of positive control group considered 100% cytotoxicity.…”
Section: -Meo-pvpmentioning
confidence: 61%
“…Assessment of the ability of drugs of abuse to increase spontaneous locomotor activity of rodents is an important tool to predict their abuse liability, as it is recognized that both reinforcing/rewarding properties are mediated by an increase of DA-ergic neurotransmission in the striatum, which is also manifested in the locomotor stimulation (Baumann et al 2011;Blough et al 2019;Bonano et al 2015). Therefore, it is recommended that any CNS-active drug should be evaluated for its abuse potential both using in vitro and in vivo pharmacological models (FDA 2017;Mdege et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clephedrone (4-Chloromethcathinone; 4-CMC) is a monoamine transporter substrate (releaser) similar potency for SERT and DAT (Blough et al, 2018;Eshleman et al, 2013;2017), although one study reported that clephedrone was 3-fold more potent at releasing dopamine than serotonin, with equal efficacy (Bonano et al, 2015). However, when looking at time course, it is interesting to note that whereas clephedrone produced a large increase in DA levels, the onset was slow (Suyama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ketones like propiophenone and its derivatives are important drug precursors . These compounds can generate many structures from brominated intermediates and then by the substitution for another building block or functional group.…”
Section: Introductionmentioning
confidence: 99%